The Impact of Histological Annotations for Accurate Tissue Classification Using Mass Spectrometry Imaging - Juliana Pereira Lopes Gonçalves; Christine Bollwein; Anna Melissa Schlitter; Benedikt Martin; Bruno Märkl; Kirsten Utpatel; Wilko Weichert; Kristina Schwamborn (Metabolites, 2021)
Knowing the precise location of analytes in the tissue has the potential to provide information about the organs’ function and predict its behavior. It is especially powerful when used in diagnosis and prognosis prediction of pathologies, such as cancer. Spatial proteomics, in particular mass spectrometry imaging, together with machine learning approaches, has been proven to be a very helpful tool in answering some histopathology conundrums. To gain accurate information about the tissue, there is a need to build robust classification models. We have investigated the impact of histological annotation on the classification accuracy of different tumor tissues. Intrinsic tissue heterogeneity directly impacts the efficacy of the annotations, having a more pronounced effect on more heterogeneous tissues, as pancreatic ductal adenocarcinoma, where the impact is over 20% in accuracy. On the other hand, in more homogeneous samples, such as kidney tumors, histological annotations have a slenderer impact on the classification accuracy.